Lipoid proteinosis in a six-year-old child - Surajit Nayak; Basanti Acharjya (Wolters Kluwer Medknow Publications, 2012)
Lipoid proteinosis (LiP) (OMIM 247100) is a rare autosomal recessive disease caused by loss of function mutations in the extracellular matrix protein 1 gene, ECM1, on chromosome 1q21. Clinically characterized by hoarseness in early infancy, followed by waxy papules and plaques on the face and body along with pox-like and acneiform scars. We report here a 6-year-old female child with LiP, who presented to our OPD for recurrent vesicullobullous lesions and beaded lesions over eyelid margins.